Household Survey Panel: How Much Do Following Rules Affect Sample Size - Watson, N; Schonlau, M; Kroh, M (My University, 2011)
In household panels, typically all household members are surveyed. Because household composition changes over time, so-called following rules are implemented to decide whether to continue surveying household members who leave the household (e.g. former spouses/partners, grown children) in subsequent waves. Following rules have been largely ignored in the literature leaving panel designers unaware of the breadth of their options and forcing them to make ad hoc decisions. In particular, to what extent various following rules affect sample size over time is unknown. From an operational point of view such knowledge is important because sample size greatly affects costs. Moreover, the decision of whom to follow has irreversible consequences as finding household members who moved out years earlier is very difficult. We find that household survey panels implement a wide variety of following rules but their effect on sample size is relatively limited. Even after 25 years, the rule “follow only wave 1 respondents” still captures 85% of the respondents of the rule “follow everyone who can be traced back to a wave 1 household through living arrangements”. Almost all of the remaining 15% live in households of children of wave 1 respondents who have grown up (5%) and in households of former spouses/partners (10%). Unless attrition is low, there is no danger of an ever expanding panel because even wide following rules do not typically exceed attrition.
Keywords: Surveys and Survey Methodology -- Fieldwork; Surveys and Survey Methodology -- Survey response; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Survey response; Fieldwork; Surveys and Survey Methodology